An analysis of nominal figurative expressions in Tan Swie Hian Fables / Peh Yoke Peng - Peh , Yoke Peng (2018)
This study examines the nominal figurative expressions in Tan Swie Hian Fables. Source-to-target domain mapping is applied to find out the metaphorical expressions and provide clarity to the structure of conceptual metaphor in all 100 fables. The theoretical framework is based upon that done by George Lakoff and Mark Johnson (1980) for the analysis of nominal figurative expression in this fable. The study provides the first effort to analyse conceptual metaphors found in Tan Swie Hian Fables. Cognitive and critical approaches will be applied to this metaphor analysis. The nominal figurative expressions in this study are presented to the reader for the framework of the experience and knowledge in this fable. From the metaphor analysis, it will guide the reader to know more about Tan Swie Hian’s main ideas.